Analysis and assessment of the influence coaches' formative profile has on young footballers - Susana Irazusta Adarraga; Óscar González Rodríguez; Izaskun Azpillaga Arrechea; José Antonio Arruza Gabilondo (FEADEF, 2012)
The aim of this research is to analyze and assess the formative profile of football coaches, based on Nicholls' Goal Theory (1984), Bandura's Self-efficiency Theory (1986) and Deci and Ryan's Self Determination Theory (1985). We selected three coaches from the lower categories of Real Sociedad S.A.D. and 4 players (aged 15 to 19) from each of their teams. We selected the players depending on the time they participated in the competition, to represent the footballers that play almost every minute, the ones that play around 75% of the minutes and the ones who play the smallest amount of minutes (more or less 50%). At the end of the season, these players filled in the questionnaire of Perceived Formative Climate, which involves four different variables (Motivational Climate, Trust in the players, Communication and Decisional style). The results we obtained show that there are significant differences (pd».05) in the perception of players with regard to the formative climate of their coaches. Specifically, we found these differences in four of the seven dimensions composing the formative climate (Individual Mastery Climate, Emotional Communication, Decisional Style and Reactive Communication). These results emphasize how important are coach's criteria and the way he/she communicates with players regarding the formative quality and sports experience. Moreover, these conclusions also suggest that it is necessary to tackle it from a multidimensional perspective to be able to analyze it in depth and within the context